2001
DOI: 10.1046/j.1537-2995.2001.41111421.x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent transfusion‐related acute lung injury

Abstract: The first episode of TRALI seems to be due to the action of HLA-A2 and granulocyte-specific IgM antibodies. The second episode may have been due to the action of lipid neutrophil-priming agents in the donors' units in association with the patient's underlying pulmonary condition (i.e., recovering from lung injury). TRALI can recur if a patient requires further transfusion support shortly after an initial episode of TRALI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 33 publications
1
31
0
1
Order By: Relevance
“…An earlier study reported leucocyte antibodies in 89% and lymphocyte antibodies in 72% of 36 patients with a clinical syndrome resembling TRALI [46]. Other studies have demonstrated antigranulocyte antibodies specific for HNA-3a (5b) [40,47], anti-NB2 [48], HNA-2a (NB1) [39] and anti-A2 [49] in the implicated donor units.…”
Section: The Antibody-mediated Modelmentioning
confidence: 94%
“…An earlier study reported leucocyte antibodies in 89% and lymphocyte antibodies in 72% of 36 patients with a clinical syndrome resembling TRALI [46]. Other studies have demonstrated antigranulocyte antibodies specific for HNA-3a (5b) [40,47], anti-NB2 [48], HNA-2a (NB1) [39] and anti-A2 [49] in the implicated donor units.…”
Section: The Antibody-mediated Modelmentioning
confidence: 94%
“…[9][10][11][12] Despite this, some enigmas remain, as not all leukocyte antibodies cause TRALI in recipients with the cognate antigen 13,14 and some antibodies (eg, anti-human neutrophil antigen-3a [HNA-3a] and anti-human leukocyte antigen-A2 [HLA-A2]) are associated with clinically more severe TRALI reactions. 7,8,15,16 Animal models have contributed significantly to our understanding of the immune mechanisms of TRALI. For example, an ex vivo rabbit lung model of TRALI demonstrated that complement was required to induce anti-HNA-3a-mediated neutrophil activation and increased pulmonary vascular permeability.…”
Section: Introductionmentioning
confidence: 99%
“…14 TRALI may recur in the same patient, but this appears to be rare. 15 Indeed there are only seven reported cases of recurrence in the literature. 10 If TRALI is suspected, the hospital blood bank should be contacted.…”
Section: Discussionmentioning
confidence: 99%